International student acculturation at the University of Jyvaskyla - Kruid, Benjamin (2017)
This study examined the perception of belonging and community integration of international students. The study used the International Friendly Campus Scale to examine various aspects of community integration by international students and used University of Jyväskylä as a case study. The data is drawn from students had had been living in Jyväskylä for at least one year. This study looks at how campus discrimination, international office services, social engagement, and academic services at the University of Jyvaskyla impact how well international students identify with the institution. The degree to which students identify with the institution was then used to interpret international student acculturation at the university. The results of the factor analysis show a transfer of the scale from the original context to Jyvaskyla is appropriate. A regression analysis comprised of the survey categories and two of the student descriptive variables show the contributions made by the survey categories are significant contributions to student identification and acculturation. The implications of this study impact international student acculturation and the confirmation that the International Friendly Campus Scale can be transferrable with a fairly high degree of accuracy between contexts as different as the Midwestern United States and Finland. Use of this scale would be of benefit for universities either with large international student populations or courting international students.